Musical performance: a philosophical study - Godlovitch, Stan (Oxon Routledge, 1998)
Most music we hear comes to us via a recording medium on which sound has been stored. Such remoteness of music heard from music made has become so commonplace it is rarely considered.Musical Performance: A Philosophical Study considers the implications of this separation for live musical performance and music-making. Rather than examining the composition or perception of music as most philosophical accounts of music do, Stan Godlovitch takes up the problem of how the tradition of active music playing and performing has been challenged by technology and what problems this poses for philosophical aesthetics. Where does does the value of musical performance lie? Is human performance of music a mere transfer medium? Is the performance of music more expressive than recorded music? Musical Performance poses questions such as these to develop a fascinating account of music today. musicians - but via some recording medium on which sound has been stored.